2016
DOI: 10.1016/j.neuroscience.2016.06.022
|View full text |Cite
|
Sign up to set email alerts
|

Female sex and obesity increase photophobic behavior in mice

Abstract: Migraine affects predominantly women. Furthermore, epidemiological studies suggest that obesity is a risk factor for migraine and this association is influenced by sex. However, the biological basis for this bias is unclear. To address this issue, we assessed light avoidant behavior, a surrogate of photophobia, in female C57BL/6J mice fed regular diet (RD) or high fat diet (HFD, 60% kcal from fat). We first assessed sex differences in basal photophobia in 20-25 week old mice and found that both obese and lean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 34 publications
2
8
0
Order By: Relevance
“…Sensory information traveling from periosteal, meningeal, cutaneous or bony tissues of the head potentially undergoing inflammatory processes after concussion follow the same path and have points of convergence within the trigeminal pathway as that of the vibrissae, which are used by rodents to explore their environment. A connection between the whiskers and the trigeminal pain system has been demonstrated behaviorally in mice [ 52 ]. Convergence of neurons between the potentially inflamed structures and those not injured or inflamed (ie.…”
Section: Discussionmentioning
confidence: 99%
“…Sensory information traveling from periosteal, meningeal, cutaneous or bony tissues of the head potentially undergoing inflammatory processes after concussion follow the same path and have points of convergence within the trigeminal pathway as that of the vibrissae, which are used by rodents to explore their environment. A connection between the whiskers and the trigeminal pain system has been demonstrated behaviorally in mice [ 52 ]. Convergence of neurons between the potentially inflamed structures and those not injured or inflamed (ie.…”
Section: Discussionmentioning
confidence: 99%
“…Several animal studies have explored the effects of obesity on migraine-like behaviour in mice, where photophobia and nocifensive behaviours have been assessed. It was demonstrated that both obese female and male mice develop a very modest basal photophobia that was accentuated by facial administration of capsaicin, a TRPV1 agonist and nociceptive [98,99]. The degree of photophobia was weight dependent in high fat diet males, but not in female mice [98,99].…”
Section: Endocrinology and Body Composition In Migraine And Iihmentioning
confidence: 99%
“…It was demonstrated that both obese female and male mice develop a very modest basal photophobia that was accentuated by facial administration of capsaicin, a TRPV1 agonist and nociceptive [98,99]. The degree of photophobia was weight dependent in high fat diet males, but not in female mice [98,99]. This photophobic phenotype is replicated in genetically obese ob/ob mice on a normal diet, whereas lean mice on a high fat diet did not exhibit this behaviour, suggesting that excess adiposity confers a photophobic phenotype rather than a high fat diet [98].…”
Section: Endocrinology and Body Composition In Migraine And Iihmentioning
confidence: 99%
“…32 Further, recent animal data have demonstrated that obesity is associated with both an augmented basal and acute trigeminovascular response to stimulation and may be capable of priming the trigeminovascular system to be responsive to otherwise innocuous stimuli. 38,39 Finally, it is also possible other factors such as changes in physical activity, medications, the presence of comorbidities (e.g., depression), or other medical conditions contribute to the relationship between migraine and obesity and underweight status.…”
Section: Neurology 88 May 9 2017 1801mentioning
confidence: 99%